Groundwater salinity mapping of the Belgian coastal zone to improve local freshwater storage availability - Vandevelde Dieter; van Baaren Esther; Delsman Joost; Karaoulis Marios; Oude Essink Gualbert; de Louw Perry; Vermaas Tommer; Pauw Pieter; de Kleine Marco; Thofte Sara; Teilmann Rasmus; Walraevens Kristine; et al. (E3S Web of Conferences, 2018)
In the European TOPSOIL project, countries around the North Sea are searching for solutions for climate related threats. They explore the possibilities of using the topsoil layer to solve current and future water challenges. The main objective is to improve the climate resilience of the water management of the topsoil and shallow aquifers in the North Sea region. TOPSOIL is supported by the Interreg VB North Sea Region program in line with priority 3 of the program: ‘Sustainable North Sea Region, protecting against climate change and preserving the environment’. The Belgian part of this project, called FRESHEM for GO-FRESH Vlaanderen (‘FREsh Salt groundwater distribution by Helicopter ElectroMagnetic survey for Geohydrological Opportunities FRESH water supply’), focuses on mapping the salinity distribution of groundwater using airborne electromagnetics and aims to look into a number of measures that could increase the availability of freshwater for agriculture in the polder area. Two pilot projects will evaluate the possibilities for freshwater storage and aims to specify what measures can be taken to achieve this. Together with the other water users and water managers, The Flanders Environment Agency wants to prepare a plan for the realization of one or more pilot projects that can improve the availability of freshwater.